A vocational training system based on competencies - Blas Aritio, Francisco de Asís (Avances en Supervisión Educativa, 2007)
Teaching and learning methods based on competencies, as opposed to more traditional approaches, which are based on the mere transmission of knowledge, involve reviewing curricular content so as to cover more instrumental elements, including the teaching of procedural techniques, attitudes and employment skills.These newly designed curricula are comprised of the same constituents as the so referred traditional ones: objectives, subject matter's content and assessment criteria. Assessment is individual and cumulative. But one of the most reiterated criticisms comes from the fact that the above mentioned curricular constituents have not been developed by teaching experts but by people outside the education world.Others take a critical view by denying that professional skills can be divided into basic standards, artificially separated into isolated units, whose addition may constitute a "competency unit". Finally, another relevant problem is related to one of the most conclusive and classical matters of teaching approaches: the problem of achieving successful learning transfer.